Developing 21st Century Skills: Critical Thinking Skills in Case-Based Learning in Social Studies - Sujarwo, Sujarwo; Safitri, Desy; Ibrahim, Nurzengky (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2022)
The industrial revolution 4.0 that occurred in the 21st century has brought about the needs and challenges of life that are different from the previous century. Changes that occur so quickly and are full of disruption due to the development of information technology require mastery of skills relevant to the needs of the 21st century. One of the skills needed is critical thinking skills. An alternative that can be used in developing critical thinking skills is through case-based blended learning. Through case-based blended learning in social science learning, students can improve their critical thinking skills by seeking and finding knowledge through reality and dynamics in real life, social interaction and collaboration.